Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/su13073741
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Human Visual Perception in Tunnel Portals

Abstract: To study the characteristics of light and dark adaptation in tunnel portals, and to determine the influencing factors in light–dark vision adaptation, basic tunnel lighting and linear design data were obtained. In this study, we used a light-shielded tent to simulate the dark environment of a tunnel, observe the driver recognition time for target objects during the light–dark adaptation process, and analyze the light–dark adaptation time of human vision. Based on the experimental data, we examined the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The experiment was also carried out on the Expressway A, and the experimental period when the traffic flow was relatively stable was selected as much as possible, which aimed to minimize the interference with the data results. Considering that studies have shown that drivers’ visual adaptation process is related to strong changes in light intensity, the experiment was selected to be carried out at noon in clear weather [ 46 , 47 ].…”
Section: Engineering and Datamentioning
confidence: 99%
“…The experiment was also carried out on the Expressway A, and the experimental period when the traffic flow was relatively stable was selected as much as possible, which aimed to minimize the interference with the data results. Considering that studies have shown that drivers’ visual adaptation process is related to strong changes in light intensity, the experiment was selected to be carried out at noon in clear weather [ 46 , 47 ].…”
Section: Engineering and Datamentioning
confidence: 99%
“…This method is widely used in multi-objective scheme selection, such as for highways, electric power, etc. [17,[36][37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…In addition, each subjective or objective weighting method is applied only to assign weights to indexes, which ignores the influences of objective factors, evaluators' opinions, and analyzers' preferences on indexes. As a result, the highway route scheme determined is not optimal [17,18]. In addition, without the help of computers and intelligent technology, these methods cannot adapt to evaluation by a large group, and no feasible algorithm is applied to scheme optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding tunnel safety, the relationship between drivers' physiological and behavioral characteristics and tunnel safety has aroused much attention from scholars. The drivers' electrocardiogram (ECG) and speed variation characteristics in various sections of the tunnel (entrance, exit and internal section) and the visual variation characteristics of drivers at the entrance and exit of the tunnel [15][16][17][18][19][20] and tunnel environment [21][22][23] have been intensively discussed in the field of tunnel safety. For instance, the "black hole" and "white hole" effects caused by the rapid change in illumination at the tunnel entrance and exit have an impact on drivers' visual adaptability [24][25][26].…”
Section: Drivers' Physiological and Behavioral Characteristics And Tunnel Safetymentioning
confidence: 99%